Dialogic Scaffolding as a Strategic Pedagogical Framework: Developing EFL Speaking Competence through Mediated Deliberation - Ayu Meita Puteri Siregar (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2026)
This study investigates the effectiveness of the Dialogic Scaffolding as a Strategic Pedagogical Framework (DSSPF) in enhancing EFL speaking competence among first-year university students. Grounded in Vygotsky’s sociocultural theory and contemporary language learning strategy research, the DSSPF integrates systematic strategic instruction within dialogic deliberation tasks (Vygotsky, 1978; Rose et al., 2024). The research employed a mixed method embedded design involving 20 Basic Speaking students at STAIN Mandailing Natal over 15 weeks. Data were collected through classroom observations (15 sessions), pre-post speaking assessments, semi-structured interviews, and student reflective journals. Quantitative analysis revealed significant improvements in strategic speaking competence, with a large effect size in communication strategy use frequency (t (19) = 4.86, p < .001, d = 1.08) and speech rate (t (19) = 3.92, p < .001, d = 0.87). Qualitative analysis identified three key lecturer mediation moves, namely meta-strategic prompting, dialogic weaving and contingent feedback, that facilitated students’ transition from formulaic to strategic discourse production. Thematic analysis of interview data yielded five emergent themes: developing strategic awareness, reducing speaking anxiety, growing dialogic confidence, appreciating localized content and recognizing the lecturer’s role as a strategic mediator. The DSSPF offers a practical pedagogical model for integrating language learning strategies into communicative language teaching, addressing the persistent gap between strategy instruction and authentic language use in EFL contexts.